Implementasi Kurikulum Berbasis Al-Qur’an di SDIT At-Tawazun - Hendi Supandi; Siti Qomariah; Toha Suryana; Tedi Tedi (Lembag, 2025)
This paper aims to examine the concept of integrated Islamic education based on the Qur'an at SDIT AT-Tawazzun, which focuses on building student character through an educational approach based on the values ​​of the Qur'an. The research method used is a qualitative approach with descriptive analysis, collecting data through observation, interviews and documentation studies regarding the implementation of the Qur'ani-based curriculum. The research results showed that the learning methods applied, including tahfidz Al-Qur'an, tadabbur Al-Qur'an, and instilling Qur'anic moral values, succeeded in increasing students' intellectual intelligence and morals. Apart from that, parental involvement and various evaluation methods also play an important role in achieving educational goals at the school.